Determining Permissiveness of RVFV MP-12 in Porcine Macrophage Lineage Cells - Cox, Victoria G. (My University, 2016)
Rift Valley fever virus (RVFV) has a significant impact on ruminants in Africa, leading to high mortality in young animals, frequent abortions in pregnant females, and disease in humans. Although ruminants are the animals chiefly affected by RVFV, it has been shown to infect other animals that could have an impact on its enzootic cycle. Pigs are a common livestock animal that has not been deeply investigated although it has been shown that pig species can possess antibodies to RVFV after inoculation. The objective of this study was to determine if two different porcine derived cell lines of macrophage lineage were permissive to MP-12 virus, an attenuated form of RVFV, due to the lack of information about porcine involvement in infection cycles. Infections at variable multiplicity of infections (MOIs) and viral kinetics showed these cells to be permissive. There was a marked difference in the amount of cytopathic effect (CPE) between the two cell lines with the cells that are more like monocytes showing more CPE than the more macrophage like cells. Both cell lines produced titers ranging from 103 to 106 plaque forming units/mL (pfu/mL) with comparable titers between the two cell lines. This work serves as a beginning point for deeper investigations into the ability of porcine species to be infected by this disease.